2014
DOI: 10.1002/jbmr.2380
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease Autoimmunity and Hip Fracture Risk: Findings from a Prospective Cohort Study

Abstract: The impact of celiac disease autoimmunity on bone health is unclear. We investigated the associations of seropositivity for tissue transglutaminase antibodies (tTGA) and endomysial antibodies (EMA) with incident hip fractures using data from a prospective cohort study, Mini-Finland Health Survey. Baseline serum samples, taken in 1978-80, were tested for tTGA and EMA. Incident hip fractures up to the year 2011 were ascertained from a national hospitalization register. Associations between seropositivity and hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Nonetheless, we cannot disregard the possibility that these autoantibodies are an additional mechanism through which decreased bone mass occurs in celiac disease. This is further supported by observations of increased anti EMA seroprevalence amongst a premenopausal non-celiac female sample with low BMD ( Heikkilä et al, 2015 ).…”
Section: Autoimmunity and Osteoporosissupporting
confidence: 67%
“…Nonetheless, we cannot disregard the possibility that these autoantibodies are an additional mechanism through which decreased bone mass occurs in celiac disease. This is further supported by observations of increased anti EMA seroprevalence amongst a premenopausal non-celiac female sample with low BMD ( Heikkilä et al, 2015 ).…”
Section: Autoimmunity and Osteoporosissupporting
confidence: 67%
“…In a large retrospective Danish study [44], low BMD only occurred in the CD patients with increased TG2 antibody levels. A prospective cohort study from Finland [20] found that those with positive TG2 antibodies had an 1.6 to 2.2-fold risk (HR) of hip fracture compared to seronegative individuals during 30 years follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated population prevalence of CD in Northern Europe is (1.0-1.5 %) [19]. While more cases are being diagnosed as a consequence of increased awareness, studies indicate that most patients with CD still remain undiagnosed [3,20]. An enzyme-linked immunosorbent assay (ELISA) for IgA TG2 has a sensitivity of 88-98 % and specificity of 82-97% in the diagnosis of CD [21,22], however, duodenal biopsy is warranted to confirm.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 Pre-treatment serum vitamin D and other nutrient markers such as iron, prealbumin, and folate are significantly lower in CD individuals with villous atrophy (versus Marsh I–II histology) 3 and similarly osteopenia in CD appears to correlate with the degree of histologic severity 4 , evidenced by a greater frequency of osteopenia seen in the setting of villous atrophy rather than in potential CD where small bowel inflammation is absent. 5, 6 Although malabsorption, disturbances in parathyroid hormone secretion 79 and a chronic inflammatory state 10, 11 may be responsible for risks of bone fragility in untreated patients, bone mineral density (BMD) generally improves upon treatment of CD with a gluten-free diet (GFD) 12, 13 , particularly in children diagnosed with CD at a young age 7 , suggesting that underlying disturbances in bone mineralization may be corrected through reversal of malabsorption with treatment.…”
mentioning
confidence: 99%